Topical apigenin improves epidermal permeability barrier homoeostasis in normal murine skin by divergent mechanisms. Issue 3 (12th March 2013) - Hou, Maihua; Sun, Richard; Hupe, Melanie; Kim, Peggy L.; Park, Kyungho; Crumrine, Debra; Lin, Tzu‐Kai; Santiago, Juan Luis; Mauro, Theodora M.; Elias, Peter M.; Man, Mao‐Qiang
Abstract The beneficial effects of certain herbal medicines on cutaneous function have been appreciated for centuries. Among these agents, chrysanthemum extract, apigenin, has been used for skin care, particularly in China, for millennia. However, the underlying mechanisms by which apigenin benefits the skin are not known. In this study, we first determined whether topical apigenin positively influences permeability barrier homoeostasis, and then the basis thereof. Hairless mice were treated topically with either 0.1% apigenin or vehicle alone twice daily for 9 days. At the end of the treatments, permeability barrier function was assessed with either an electrolytic water analyzer or a Tewameter. Our results show that topical apigenin significantly enhanced permeability barrier homoeostasis after tape stripping, although basal permeability barrier function remained unchanged. Improved barrier function correlated with enhanced filaggrin expression and lamellar body production, which was paralleled by elevated mRNA levels for the epidermal ABCA12. The mRNA levels for key lipid synthetic enzymes also were upregulated by apigenin. Finally, both cathelicidin‐related peptide and mouse beta‐defensin 3 immunostaining were increased by apigenin. We conclude that topical apigenin improves epidermal permeability barrier function by stimulating epidermal differentiation, lipid synthesis and secretion, as well as cutaneous antimicrobial peptide production. Apigenin could be useful for the prevention and treatment of skin disorders characterized by permeability barrier dysfunction, associated with reduced filaggrin levels and impaired antimicrobial defenses, such as atopic dermatitis.